Quantifying transmission of highly pathogenic and low pathogenicity H7N1 avian influenza in turkeys. - Roberto A Saenz; Steve C Essen; Sharon M Brookes; Munir Iqbal; James L N Wood; Bryan T Grenfell; John W McCauley; Ian H Brown; Julia R Gog (PLoS ONE)
Outbreaks of avian influenza in poultry can be devastating, yet many of the basic epidemiological parameters have not been accurately characterised. In 1999-2000 in Northern Italy, outbreaks of H7N1 low pathogenicity avian influenza virus (LPAI) were followed by the emergence of H7N1 highly pathogenic avian influenza virus (HPAI). This study investigates the transmission dynamics in turkeys of representative HPAI and LPAI H7N1 virus strains from this outbreak in an experimental setting, allowing direct comparison of the two strains. The fitted transmission rates for the two strains are similar: 2.04 (1.5-2.7) per day for HPAI, 2.01 (1.6-2.5) per day for LPAI. However, the mean infectious period is far shorter for HPAI (1.47 (1.3-1.7) days) than for LPAI (7.65 (7.0-8.3) days), due to the rapid death of infected turkeys. Hence the basic reproductive ratio, [Formula: see text] is significantly lower for HPAI (3.01 (2.2-4.0)) than for LPAI (15.3 (11.8-19.7)). The comparison of transmission rates and [Formula: see text] are critically important in relation to understanding how HPAI might emerge from LPAI. Two competing hypotheses for how transmission rates vary with population size are tested by fitting competing models to experiments with differing numbers of turkeys. A model with frequency-dependent transmission gives a significantly better fit to experimental data than density-dependent transmission. This has important implications for extrapolating experimental results from relatively small numbers of birds to the commercial poultry flock size, and for how control, including vaccination, might scale with flock size.